Historic Mortars Advances in Research and Practical Conservation - Hughes, John J.; Válek, Jan; Groot, Caspar J. W. P. (Springer International Publishing : Imprint: Springer, 2019)
This book presents a state of the art in mortar characterisation, experimentation with and applications of new mortars for conservation and repair of historic buildings. This volume includes the following topics: characterisation of historic mortars (methods, interpretation, application of results), development of new materials for conservation (compatibility, durability, mix designs), the history of mortar technology and fundamental experimental studies of material properties. The papers have been selected from those presented at the 3rd Historic Mortars Conference, held in Glasgow, Scotland, September 11-14th 2013. All the papers here underwent a two stage peer review process, for the conference and again for this volume. In some cases this has resulted in a revision and updating of content.